STUDY ON INTRAORAL DISTRIBUTION OF DENTAL PLAQUE - Cristian Funieru; Ruxandra Ionela Sfeatcu (Amaltea Medical Publishing House, 2018)
Introduction. Discovering the dental plaque accumulation model is important for establishing the oro-dental pathological pattern as well as for establishing individualized prevention programs. Materials and method. Our work is a pilot study developed on a group of 15 patients aged 20-38 years, which involved 223 teeth (892 dental surfaces). The O'Leary plaque index was used in order to assess the dental plaque distribution (accumulation pattern). Results. The dental plaque was found mostly on the maxillary dental surfaces, especially on proximal surfaces (consistently than the vestibular or oral ones). Conclusions. Individualized oral preventive programs should be based on this general pattern (dental plaque accumulation on proximal surfaces) as well as individual risk factors: dental crowding, increased sweets consumption etc.